2001
DOI: 10.1021/jp010642o
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Carbon Nanotubes and Graphite in Liquid Ammonia

Abstract: We have prepared hydrogenated single-wall and multiwall carbon nanotubes, as well as graphite, via a dissolved metal reduction method in liquid ammonia. The hydrogenated derivatives are thermally stable up to 400°C. Above 400°C, a characteristic decomposition takes place accompanied with the simultaneous formations of hydrogen and a small amount of methane. Transmission electron micrographs show corrugation and disorder of the nanotube walls and the graphite layers due to hydrogenation. The average hydrogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
198
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(206 citation statements)
references
References 38 publications
5
198
0
3
Order By: Relevance
“…It was also demonstrated that metallic SWNTs showed higher reactivity in these types of reactions than semiconductive SWNTs, which would allow CNT separation [134]. [135], CNTs were reacted with strong nucleophilic reagents such as nucleophilic carbene [128], sec-butyllithium [136], polymeric carbanions [137] and Birch reduction reagents (lithium/1,2-diaminoethane [108] or lithium/ammonia [138]) to form various f -CNTs (Scheme 3.4).…”
Section: Radical Additionmentioning
confidence: 99%
“…It was also demonstrated that metallic SWNTs showed higher reactivity in these types of reactions than semiconductive SWNTs, which would allow CNT separation [134]. [135], CNTs were reacted with strong nucleophilic reagents such as nucleophilic carbene [128], sec-butyllithium [136], polymeric carbanions [137] and Birch reduction reagents (lithium/1,2-diaminoethane [108] or lithium/ammonia [138]) to form various f -CNTs (Scheme 3.4).…”
Section: Radical Additionmentioning
confidence: 99%
“…As a response, new energies, e.g., solar energy, wind energy, nuclear energy, geothermal energy, tidal energy, bioenergy, and hydrogen energy, have been intensively investigated for the replacement of traditional energy. Hydrogen is a promising candidate for the next generation of energy careers due to its high energy conversion efficiency, zero emission, renewable, and abundant resources [1][2][3][4]. A commercially available hydrogen storage material with low-cost, high volumetric and gravimetric hydrogen densities, fast sorption kinetics, and safe and efficient storage is necessary for the development of a hydrogen economy for transportation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modification of the surface of nanotube is expected to enhance the interface shear strength. Researchers have successfully modified the surface of CNTs with different functional groups [28][29][30] and the use of these fibers for composites is expected to enhance the mechanical properties [31,32]. In an earlier study we have used molecular dynamics simulations of pullout tests to show that the chemical modification of nanotube surfaces through functionalization is expected to enhance the interface strength significantly [32].…”
Section: Introductionmentioning
confidence: 99%